2018
DOI: 10.1073/pnas.1717474115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of species differences via in vitro crosses in mouse embryonic stem cells

Abstract: SignificanceHow species differ from each other is a key question in biology. However, genetic mapping between species often fails because of sterile hybrid crosses. Here, we have developed a technique called in vitro recombination to circumvent breeding. We induced genetic reshuffling through mitotic recombination with the drug ML216 and mapped trait variations in a dish. Starting with hybrid embryonic stem cells between the Mus musculus laboratory mouse and Mus spretus spanning ∼1.5 million years of divergenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This translates to an endogenous rate of ∼0.8 recombination events per cell per generation and an increased rate of approximately one recombination event per cell per generation after ML216 treatment. These apparent rates in allotetraploid cells are substantially higher than previously reported mitotic recombination rates in diploid human and mouse embryonic stem cells [0.01 to 0.04 recombination events per cell per generation after ML216 treatment; SI Appendix, Supplemental Materials and Methods (10,11,29)]. Further investigation will be required to assess whether ML216 significantly increases the rate of interspecific recombination and whether other small molecules such as camptothecin can also increase the rate of recombination events between human and chimpanzee chromosomes in allotetraploid iPSCs.…”
Section: Differential Gene Expression and Allele-specific Gene Expressionmentioning
confidence: 66%
See 2 more Smart Citations
“…This translates to an endogenous rate of ∼0.8 recombination events per cell per generation and an increased rate of approximately one recombination event per cell per generation after ML216 treatment. These apparent rates in allotetraploid cells are substantially higher than previously reported mitotic recombination rates in diploid human and mouse embryonic stem cells [0.01 to 0.04 recombination events per cell per generation after ML216 treatment; SI Appendix, Supplemental Materials and Methods (10,11,29)]. Further investigation will be required to assess whether ML216 significantly increases the rate of interspecific recombination and whether other small molecules such as camptothecin can also increase the rate of recombination events between human and chimpanzee chromosomes in allotetraploid iPSCs.…”
Section: Differential Gene Expression and Allele-specific Gene Expressionmentioning
confidence: 66%
“…induced by Cas9 and guide RNAs (gRNAs) designed to alter particular locations in the genome. Mutations and chemical inhibitors of the Bloom Syndrome helicase gene (BLM) have been used to recover homozygous mutants in somatic cell gene screens (9,10) or to induce recombination between chromosomes of distantly related mouse strains for studies of the genomic basis of evolutionary differences (11). The ability to induce breaks at particular loci with CRISPR-Cas9 has also made it possible to choose both the location and the direction of recombination between genomes in nonmeiotic cells, enabling high-resolution mapping without traditional crosses in yeast (12).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Lazzarano et al showed that ML216 induces mitotic crossover in mouse ESCs. They also reported that transient suppression of the BLM protein did not increase aneuploidy [13]. The procedure used to isolate positive clones generated with the BLM inhibitor ML216 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the field has advanced largely on the strength of candidate-based studies that implicate a single variant gene in an interspecific trait 5,6 , with the complete genetic architecture often remaining unknown. Against the backdrop of a few specialized introgression [7][8][9][10] and molecular-evolution 11 techniques available in the field, dissection of complex trait differences between species has remained a key challenge.…”
mentioning
confidence: 99%